Case report: Complete response to pembrolizumab in a liver metastatic colon adenocarcinoma patient with a novel likely pathogenic germline MSH2 mutation - Xu, Yanjie; Li, Qin; Zhao, Jiemin; Ni, Xuefeng; Li, Ping; Hu, Wenwei (Frontiers in Immunology, 2022)
Lynch syndrome (LS) is a genetic disorder mainly, caused by germline mutations in mismatched repair (MMR) genes: MSH2, MLH1, MSH6 and PMS2 or deletions of the epithelial cell adhesion molecule gene (EPCAM). The patient was a 43-year-old Chinese male who underwent radical surgery and was pathologically confirmed colon adenocarcinoma in IIIB stage. After four cycles of standard adjuvant chemotherapy, the tumor reoccurred in situ with intestinal obstruction. The patient received secondary colectomy. Immunohistochemistry analysis revealed loss of MSH2 protein expression in the surgical specimen. Noticing that the patient’s mother and grandfather all were diagnosed with LS-related cancers, we collected the patient’s and his mother’s peripheral blood for genetic testing and the result showed a six base deletion of MSH2. Thus, we concluded this is a patient with LS. Subsequently, the patient accepted the pembrolizumab as the first-line systemic therapy. He achieved clinical complete response (CR) within 2 months and remained progression free for at least 2 years. The case report showed that the MSH2 mutation (c.489_494deTGGGTA) is a likely pathogenic mutation and immunotherapy (pembrolizumab) is effective for this patient.